1985
DOI: 10.1172/jci112053
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of renal prostacyclin and thromboxane A2 production in patients with systemic lupus erythematosus.

Abstract: We have examined the urinary excretion of stable immunoreactive eicosanoids in 23 female patients with systemic lupus erythematosus (SLE), 16 patients with chronic glomerular disease (CGD), and 20 healthy women. SLE patients had significantly higher urinary thromboxane B2 (TXB2) and prostaglandin (PG) E2 excretion and significantly lower 6-keto-PGFI. than did healthy women. In contrast, CGD patients only differed from controls for having reduced 6-keto-PGF1I excretion. The group of SLE patients with active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
63
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(71 citation statements)
references
References 29 publications
(31 reference statements)
6
63
2
Order By: Relevance
“…4. These present results suggest the pos sibility that blockade of the TP-receptor may exert a ben eficial action, particularly in some renal diseases, since renal vasoconstriction due to intrarenal TXA2 produc tion has been found to participate in cyclosporine nephrotoxicity (29)(30)(31) and lupus nephritis (32,33). Additionally, enhanced renal vascular reactivity to the TXA2 analogue U46619 has recently been shown in Goldblatt hypertensive rats (34,35) and genetically hypertensive rats (36).…”
Section: Discussionsupporting
confidence: 58%
“…4. These present results suggest the pos sibility that blockade of the TP-receptor may exert a ben eficial action, particularly in some renal diseases, since renal vasoconstriction due to intrarenal TXA2 produc tion has been found to participate in cyclosporine nephrotoxicity (29)(30)(31) and lupus nephritis (32,33). Additionally, enhanced renal vascular reactivity to the TXA2 analogue U46619 has recently been shown in Goldblatt hypertensive rats (34,35) and genetically hypertensive rats (36).…”
Section: Discussionsupporting
confidence: 58%
“…These actions include constriction of glomeru lar afferent and efferent arterioles, intraglomerular plate let aggregation, contraction of glomerular mesangial cells and increase of mesangial cell matrix synthesis (1,2). In creased renal TXA2 biosynthesis has been documented in a variety of animal models of renal disease (3 5) and in patients with systemic lupus erythematosus (SLE) (6). These results suggest that TXA2 plays an important role in the progression of renal diseases.…”
mentioning
confidence: 99%
“…In the patients with SLE, a significant inverse correlation was found between the urinary TXB2/6-keto-PGFIa ratio and creatinine clear ance (Ccr) (6). Moreover, recent studies have shown that a thromboxane A2-receptor antagonist (TXRA) improves renal function in patients with lupus nephritis (7,8).…”
mentioning
confidence: 99%
“…It is released at the site of vascular injury or inflammation, such as in the course of experimental nephritis (Lianos et al 1983), ureteral obstruction (Okegawa et al 1983), renal allograft rejection (Coffman et al 1985), and lupus nephritis in man (Patrono et al 1985).…”
mentioning
confidence: 99%
“…This may indicate differences between the mechanism of action of LT and various other contractile stimuli, such as ANG II, AVP and TxA2, which rapidly stimulate phospholipase activity and AA metabolism in these cells (Patrono et al 1985;Mene' and Dunn 1986). …”
mentioning
confidence: 99%